Inclusion in the top 2% of the top researchers in the scientific field of Artificial Intelligence & Image Processing - Lanitis, Andreas (My University, 2026)
Data for updated science-wide author databases of standardized citation indicators 2020 https://journals.plos.org/plosbiology/article?id=10.1371/journal.pbio.3000918
Keywords: World's Top Scientists